Water-soluble fluorescent red colorant production by Talaromyces amestolkiae - de Oliveira, Fernanda [UNESP] (2019)
The replacement of synthetic colors in food products by natural alternatives has been boosted by consumers willing to pay more for healthier products. However, the success of microbial colorants depends not only on its acceptability on the market but also its production costs. Talaromyces species can produce water-soluble red colorants induced by glucose and monosodium glutamate (MSG). In this study, the influence of several conditions was evaluated to produce natural red colorants by submerged culture of Talaromyces amestolkiae. Under optimal conditions (g/L: glucose 10, MSG 25, MgSO4 0.012, FeSO4 0.01, CaCl2 0.015; and initial pH of 5.0), a 30-fold increase in the production was achieved, reaching a red colorant production of 13.44 UA500nm. Depending on the initial pH, colorants with different hues and chroma values were obtained. Deep yellow colorants were derived from neutral and basic pH, while deep red colors were derived from acidic pH. The fluorescence spectrum of culture broth obtained before and after complexation with salts presented red colorants with yellow fluorescence spectra. The information generated in this study would be useful for the formulation of industrial media for large-scale cultivation of T. amestolkiae, which have the potential to produce Talaromyces fermented colorants for use in health foods and pharmaceutics.